Educational Learning Video Improves Learning Outcomes of Junior High School Students on Beam Materials: Video Pembelajaran Edukatif Meningkatkan Hasil Belajar Materi Balok Siswa SMP - Erpansyah; Indah Widyaningrum; Susanti, Novi (Indonesian Journal of Innovation Studies, 2025)
General Background: Mathematics education plays a critical role in shaping logical and spatial reasoning, yet many students struggle with abstract topics like three-dimensional geometry. Specific Background: In SMP Muhammadiyah Pagar Alam, learning about cuboids is hindered by teacher-centered methods and the absence of visual learning media. Knowledge Gap: Despite the growing adoption of video-based instruction, limited studies assess the classroom application of low-cost tools like the InShot app for spatial topics at the junior high level. Aims: This study aims to examine how educational videos using the InShot application contribute to student achievement in understanding cuboid material. Results: Using a Pretest-Posttest Control Group Design, the study found that students taught with educational videos achieved significantly higher posttest scores than those taught conventionally, with a large effect size (Cohen’s d = 1.24). Novelty: The research highlights a replicable, cost-effective digital approach tailored for under-resourced classrooms, showing strong cognitive and participatory benefits. Implications: Findings support the integration of short, targeted videos in mathematics instruction and align with Indonesia’s “Merdeka Belajar” initiative, offering practical strategies for enhancing classroom engagement and comprehension.ZHighlight : Posttest scores in the experimental group were significantly higher than the control. Educational video helped students grasp abstract cuboid concepts visually. Large effect size (Cohen’s d = 1.24) reflects strong learning improvements. Keywords : Educational Learning Video, Learning Outcomes, Cuboid Material, Learning Media, Experiment